Assessment Of Knowledge, Awareness, Attitude, And Practice Among Healthcare Professionals Regarding Hepatitis B Disease And Vaccination - Maha Sayil Alotaib , BUDOOR SALEM ALMATUIRI , Maha majeb M Alotaibi , Afaq Ali Alfaraj , Kholod khatem Almutairi , Maged monahi Almutairi , Aziza Abdullah Fayez Alshehri , Fahad Hamoud Aldosari; saud Hussain alshahrani , Jawaher Muhammad Binzamil , Latefh Jarallah Albogmi , Adel Ayed Al Otaibi , Mohammed kasib alanazi , Bdour Obied Alenazi , Abdualamjeed badi Almutairi (Migration Letters, 2022)
Objectives: This study aims to evaluate the knowledge, awareness, attitude, and practice of healthcare professionals (HCPs) concerning hepatitis B virus (HBV) infection and vaccination. Methods: A cross-sectional study was conducted using a pre-tested, validated questionnaire distributed among healthcare professionals . The questionnaire comprised sections on demographics, knowledge about HBV infection, awareness of hepatitis B, and attitudes toward HBV vaccination. Data analysis was performed using SAS® V9.2. Results: The study revealed that 16.5% of participants had not received the hepatitis B vaccine. However, a majority believed in the commonalit[1]y of hepatitis B (73.2%) and recognized vaccination as an effective preventive measure (75%). Barriers to vaccination included vaccine availability (48.7%) and safety concerns (37%). Among non-vaccinated participants, 31.2% considered the hepatitis B vaccine unsafe, while only 8% of vaccinated individuals shared this concern. Furthermore, 36.4% of non-vaccinated participants were unsure of the vaccine’s effectiveness, compared to 24.3% in the vaccinated group. Financial constraints were cited by 18.2% of non-vaccinated participants but only 4% of vaccinated individuals. Conclusion: While there is notable HBV vaccination coverage among HCPs in Saudi Arabia, it falls below global standards. Addressing barriers preventing non-vaccinated HCPs from getting immunized is crucial to improving vaccination rates.